2016
DOI: 10.1088/0741-3335/58/11/114001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of scrape-off layer fluctuations on first wall sputtering with the TOKAM-2D turbulence code

Abstract: Plasma material interactions on the first wall of future tokamaks such as ITER and DEMO are likely to play an important role, because of turbulent radial transport. The latter results to a large extent from the radial propagation of plasma filaments through a tenuous background. In such a situation, mean field descriptions (on which transport codes rely) become questionable. First wall sputtering is of particular interest, especially in a full W machine, since it has been shown experimentally that first wall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…The remainder of this paper is structured as follows. Section 2 introduces the TOKAM2D turbulence code [10,11,12] that is used as a reference in this work, as well as the one-equation k ⊥ model. Next, section 3 defines the enstrophy, and shows that the turbulent enstrophy (ζ ⊥ ) can be combined with the turbulent kinetic energy to obtain an improved model for the turbulent particle diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The remainder of this paper is structured as follows. Section 2 introduces the TOKAM2D turbulence code [10,11,12] that is used as a reference in this work, as well as the one-equation k ⊥ model. Next, section 3 defines the enstrophy, and shows that the turbulent enstrophy (ζ ⊥ ) can be combined with the turbulent kinetic energy to obtain an improved model for the turbulent particle diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive scientific investigations have revealed that cross-field transport of particles and heat in the scrape-off layer (SOL) of magnetically confined plasmas is caused by radial motion of blob-like filament structures [1][2][3][4][5]. This poses several challenges for future magnetic fusion energy reactors, including enhanced erosion rates of the main chamber walls [6][7][8][9][10]. There is also strong evidence that the turbulence-driven cross-field transport is related to the empirical discharge density limit [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming absence of ELMS, transient effects stemming from micro-turbulence seem unavoidable in fusion reactors. Although transient plasma loads have been simulated by laser irradiation or electron beams [25,22] the effect of turbulence on the sputtering yield and erosion overall is so far investigated theoretically only [26,27,28].…”
Section: Plasma Wall Interactionsmentioning
confidence: 99%
“…The top pictures of Figure 8. 26 show linear (left) and logarithmic (right) sputtering rate curves for mean temperature, a Gaussian distribution, a mix of mean or Gaussian and Γ distribution, and finally a pure Γ distributed temperature realization with a skewness of S = 2. The difference between mean temperature and Gaussian distribution are small and negligible when the Γ distribution is added.…”
Section: Radius [Cm]mentioning
confidence: 99%
See 1 more Smart Citation